The Training on The Making of Simple Renewable Energy Media: Attempt to Enhance Energy Literacy Among Students at Junior High School - Ketang Wiyono; Kistiono Kistiono; Evelina Astra Patriot; Frendi Ihwan Syamsudin; Nor Farahwahidah; Noor Dayana Abd Halim; Nita Arrum Sari; Roro Aisyah Purbasari (Carmin: Journal of Community Service, 2025)
This community service activity aims to train students' energy literacy through training in the creation of simple STEM-based renewable energy learning media at SMP Negeri 5Indralaya Utara. The method used was Participatory Action Research (PAR) involving 25 eighth-grade students. The stages of the activity included a preliminary survey, presentation of renewable energy and STEM material, discussion, practice in making simple renewable energy media, group presentations, pre-test, and post-tests of energy literacy. The instruments used were multiple-choice tests and observation sheets of student activities. The results of the analysis showed an average N-Gain value of 0.71 in the high category, indicating that the training was effective in improving students' energy literacy. In addition, the activity developed students' collaboration, communication, creativity, and problem-solving skills through project activities and group presentations.